“The Mic Is My Piece”: Canadian Rap, the Gendered “Cool Pose,” and Music Industry Racialization and Regulation - D’Amico, Francesca (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
Over the course of the 1980s and 1990s, Black Canadian Rap artists, many of whom are the children of Caribbean-born immigrants to Canada, employed the hyper-racialized and hyper-gendered “Cool Pose” as oppositional politics to intervene in a conversation about citizenship, space, and anti-blackness. Drawing from local and trans-local imaginings and practices, Black Canadian rappers created counter-narratives intended to confront their own sense of exclusion from a nation that has consistently imagined itself as White and rendered the Black presence hyper-(in)visible. Despite a nationwide policy of sameness (multiculturalism), Black Canadian musicians have used Rap as a discursive and dialogical space to disrupt the project of Black Canadian erasure from the national imagination. These efforts provided Black youth with the critically important platform to critique the limitations of multiculturalism, write Black Canadian stories into the larger framework of the nation state, and remind audiences of the deeply masculinized and racialized nature of Canadian iconography. And yet, even as they engaged in these oppositional politics, rappers have consistently encountered exclusionary practices at the hands of the state that have made it increasingly difficult to sustain a Black music infrastructure and spotlight Canadian Rap’s political and cultural intervention.